IDENTIFIKASI AKSES MASYARAKAT TERHADAP PEMANFAATAN SUMBERDAYA ALAM (Studi kasus di Desa Karang Tengah Kecamatan Babakan madang Kabupaten Bogor) - F Ramadhan, Teddy Arief; Susdiyanti, Tun Susdiyanti; Salampessy, Messalina L (Universitas Nusa Bangsa, 2015)
Conservation areas have an important role for the preservation of the surrounding ecosystem. Nature Park is one of the areas Conservation Areas which have an important function for life support system, preserve the diversity of plant and animal species and sustainable use of natural resources and ecosystems. The existence of the community around the region have an important role for the preservation of the region. This study aims to identify the access made public in obtaining, control and manage access to the use of natural resources around the area. The method used is a case study, in which data collection is done through in-depth interviews and participant observation. Data were analyzed using the access theory results show that the public has access to the processing area where the land around Region Natural Park of Mount Pancar has a level of encroachment or work area without permission is still quite high. Public access and utilization of acquiring land is before the area designated as TWA and ruled for generations, land control is not done specifically and communities manage the land and the potential that exists with the mastery of the blocks that have a high potential of natural resources. Seen most percentage of land cultivated by the community that is in the block of Mount Pancar as much as 24.41% and at least at the block Paniisan only 5:08%.